(untitled) - Van Draanen, Wendelin (New York, 2001)
In alternating chapters, two teenagers describe how their feelings about themselves, each other, and their families have changed over the years.
Keywords: Interpersonal relations; Fiction; Conduct of life; Fiction; Family life; Fiction; Self-perception; Fiction